The Physicochemical Characteristics of Smart Food Bars Enriched with Moringa Leaf Extract And Chitosan as An Emergency Food in Disaster Times - Hamidin Rasulu; Juharnib Juharnib (International Journal on Food, Agriculture and Natural Resources, 2021)
Emergency food products are processed food specifically designed to meet human daily needs of at least 2500 Kcal/day. One of the emergency food products, namely food bars, is a high-calorie food product, enriched with other nutrients and produced in solid form. The packaging of food bars designed in a small size makes their distribution relatively easy. The purpose of this study was to characterize the emergency food products of smart food bars by utilizing local food ingredients, including flour, mackerel fish flour, moringa leaf extract, and coconut crab chitosan at various concentrations. Furthermore, it delved into the formulation and physicochemical characterization of the best smart food bars as an emergency food by substituting cassava flour and skipjack tuna flour enriched with moringa leaf extract and coconut crab chitosan. This research used a completely randomized factorial design by combining treatments with cassava flour and skipjack fish flour as well as a combination of treatment with moringa leaf extract and the addition of coconut crab chitosan (0%, 5%, 10%, 15% 20%). The results showed that the N3 treatment (15% moringa leaf extract and chitosan) with a texture value of 2,768 N/m, color values (L*, a*, b*) were 63.35, 5.30, and 11.91, respectively. The findings also highlighted  13.29% protein, 17.80% fat, 6.55% water, 0.96% ash, 60.76% carbohydrates, 7.41% antioxidants, and total calories of 230.57 kcal. The study has concluded that the use of moringa leaf extract and coconut crab chitosan can enhance the characteristics of smart food bars as emergency food during disasters.